Last known victim - Spindler, Erica, 1957-
Summary: As the rescue efforts unfold, a grisly discovery is made - six human hands, all female, all right hands. Found beside the victim's bones is her husband's police badge. Patti knows that if she doesn't find the "Handyman" first, she will become his last known victim.